The impact of COVID-19 and locust invasion on farm households in Punjab and Sindh analysis from cross sectional surveys in Pakistan - Yamano, Takashi (Central and West Asia working papers., 2021)
This paper presents results of a survey on the impacts of the COVID19 pandemic and a simultaneous locust invasion on farmers harvests, marketing efforts, input prices, and financial needs in two provinces in Pakistan.